PENGARUH SOSIALISASI, PEMBINAAN DAN PENGAWASAN TERHADAP PENINGKATAN KESEJAHTERAAN PENERIMA ZAKAT, INFAQ DAN SEDEKAH (ZIS) PRODUKTIF (STUDI DI RUMAH ZAKAT ACEH) - Zahlul Haykal; Suazhari Suazhari; Bustamam Bustamam (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2021)
The purpose of paper is to examine the effect of socialization, coaching and supervision on the improvement of welfare for  productive ZIS recipients in Rumah Zakat Aceh. The sample in this study were 73 people whose received of productive ZIS at Rumah Zakat Aceh from in Aceh Besar District and Banda Aceh City in 2016-2019. It used Probability Sampling technique with the cluster method. Data is analyze using multiple linear regression. The results shows that the socialization, coaching, and supervision variables have a positive and significant effect on the Improvement of the Welfare of Productive ZIS Recipients even simultaneously and partially.